PINX1 and TERT are required for TNF-α-induced airway smooth muscle chemokine gene expression - Deacon, Karl; Knox, Alan J. (American Association of Immunologists, 2018)
Airway smooth muscle (ASM) cells contribute to asthmatic lung pathology with chemokine hypersecretion and increased ASM cell mass. With little recent progress in the development of asthma therapies, a greater understanding of lung inflammation mechanisms has become a priority. Chemokine gene expression in ASM cells is dependent upon NF-κB transcription factor activity. The telomerase/shelterin complex maintains chromosomal telomere ends during cell division. Telomerase is a possible cofactor for NF-κB activity, but its role in NF-κB activity in airway tissue inflammation is not known. In this study, we sought to address two key questions: whether telomerase is involved in inflammation in ASM cells, and whether components of the shelterin complex are also required for an inflammatory response in ASM cells. Telomerase inhibitors and telomerase small interfering RNA (siRNA) reduced TNF-α-induced chemokine expression in ASM cells. Telomerase siRNA and inhibitors reduced NF-κB activity. An siRNA screen of shelterin components identified a requirement for PIN2/TERF1 interacting-telomerase inhibitor 1 (PINX1) in chemokine gene expression. High-level PINX1 overexpression reduced NF-κB reporter activity, but low-level expression amplified NF-κB activity. Coimmunoprecipitation studies showed association of PINX1 and p65. Overexpression of the N terminus (2-252 aa) of PINX1, but not the C-terminal telomerase-inhibitor domain (253-328 aa), amplified TNF-α-induced NF-κB activity. GST pull-downs demonstrated that the N terminus of PINX1 bound more p65 than the C-terminal telomerase-inhibitor domain; these observations were confirmed in whole cells with N-terminal and C-terminal PINX1 immunoprecipitation. We conclude that telomerase and PINX1 are required for chemokine expression in ASM cells and represent significant new targets for future anti-inflammatory therapies for lung diseases, such as asthma.